Pengaruh Self Efficacy, Lingkungan Kerja dan Komitmen Organisasi Terhadap Kinerja Karyawan - Yeti Laelasari; Dicky Jhoansyah; Faizal Mulia Z (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Human Resources are important assets in a company to be able to obtain maximum profit, therefore self efficacy, a comfortable work environment, and good organizational commitment are needed for Employee Performance. The purpose of this study was to determine the effect of self efficacy, comfortable work environment, and organizational commitment on employee performance. The method used in this research is descriptive and associative method through quantitative approach. The population in this study was the sewing unit at PT Muara Tunggal Cibadak Sukabumi which amounted to 46 employees. The sample used in this study amounted to 46 employees of PT Muara Tunggal Cibadak Sukabumi using saturated sampling technique. The research data used in this study include primary data and secondary data, namely observation, interviews, questionnaires, literature studies, and documentation. The results of this study are There is a positive and significant influence between self efficacy variables on employee performance, there is a positive and significant influence between Work Environment variables on employee performance, and there is a positive and significant influence between organizational commitment variables on employee performance.